Potensi Nanopartikel Emas (AuNp) sebagai Sensor Kolorimetri untuk Deteksi Asam Sialat - Istatik Badi’ah, Hanim; Qomariyah, Ani (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Gold nanoparticles (AuNp) have LSPR absorption at visible wavelengths, which can be used for colorimetric sensors. The sialic acid colorimetric sensor using AuNp is an analysis based on the color change when there is an interaction between AuNp and the sialic acid analyte. The research method was carried out by synthesizing AuNp and then characterizing it using a UV-Vis spectrophotometer. The synthesis results were then used to detect sialic acid in serum samples. The success of AuNp synthesis was marked by the formation of a red AuNp colloid with a maximum wavelength of 518 nm. AuNp has potential as a colorimetric sensor for sialic acid and is characterized by a color change in the AuNp solution from red to purple. Apart from that, the spectrophotometry results show that there is a new peak at a wavelength of 655 nm. Next, AuNp was used for the detection of sialic acid in serum samples. The results of the analysis of sialic acid in serum samples showed that the recovery value was 105.6%.